2018
DOI: 10.1001/jamacardio.2018.0612
|View full text |Cite|
|
Sign up to set email alerts
|

Ticagrelor vs Clopidogrel After Fibrinolytic Therapy in Patients With ST-Elevation Myocardial Infarction

Abstract: clinicaltrials.gov Identifier: NCT02298088.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
1
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 18 publications
1
44
1
12
Order By: Relevance
“…El estudio TREAT comparó la seguridad a corto plazo de ticagrelor frente a clopidogrel en pacientes menores de 75 años que presentaron infarto agudo de miocardio con elevación del segmento ST (IAMcEST) tratados con fibrinolíticos. El objetivo primario fue valorar el sangrado mayor, según los criterios TIMI, en los primeros 30 días (19,20) .…”
Section: St-elevation Myocardial Infarctionunclassified
“…El estudio TREAT comparó la seguridad a corto plazo de ticagrelor frente a clopidogrel en pacientes menores de 75 años que presentaron infarto agudo de miocardio con elevación del segmento ST (IAMcEST) tratados con fibrinolíticos. El objetivo primario fue valorar el sangrado mayor, según los criterios TIMI, en los primeros 30 días (19,20) .…”
Section: St-elevation Myocardial Infarctionunclassified
“…Patients were randomly assigned to receive Ticagrelor or Clopidogrel as early as possible after the index event and not more than 24 hours after the event. 9 At 30 days, TIMI major bleeding had occured in 14 of 1913 patients (0,73%) receiving Ticagrelor and in 13 of 1886 patients (0,69%) receiving Clopidogrel (absolute difference 0,04%; 95% CI -0,49% to 0,58%; p<0,001 for non-inferiority). Major bleeding defined by the PLATO criteria and by the Bleeding Academic Research Consortium (BARC) types 3 to 5 bleeding was similarly showed non-inferiority.…”
mentioning
confidence: 96%
“…Thus TREAT trial was conducted to evaluate the safety of Ticagrelor in this clinical setting. 9 This multicenter, randomized, open-label with blinded end point adjudication trial, involving 3799 patients with STEMI receiving fibrinolytic therapy from 10 countries. The follow-up period is 30-day.…”
mentioning
confidence: 99%
See 2 more Smart Citations